Corundum spinel castable with low thermal conductivity and high corrosion resistance and preparation method thereof

By using raw materials such as microporous corundum, lightly burned spinel and recycling zirconium corundum bricks, combined with hydrated alumina and aluminum dihydrogen phosphate as a binding agent, a low-thermal conductivity and high-corrosion corrosion-resistant corundum spinel castable was prepared, solving the problem of reaction damage of existing materials at high temperatures, and achieving improved mechanical strength, enhanced corrosion resistance and extended service life of the material.

CN119638388APending Publication Date: 2025-03-18HUNAN XIANGGANG RUITAI TECH

Patent Information

Application Number
CN202411926481.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The reaction of existing corundum-spinel castables with molten steel and slag at high temperatures leads to material damage, and the material's thermal shock resistance and service life are insufficient.

Method used

Microporous corundum, lightly burned spinel and recycled zirconium corundum bricks are used as the main raw materials, combined with hydrated alumina and aluminum dihydrogen phosphate as the binding agent to prepare low-thermal conductivity and high corrosion-resistant corundum spinel castable.

Benefits of technology

It has achieved the mechanical strength improvement, enhanced corrosion resistance and extended service life of low thermal conductivity and high corrosion resistance of corundum spinel castable, and its performance is better than similar products in the market.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a corundum spinel castable with low thermal conductivity and high corrosion resistance and a preparation method thereof. According to the technical scheme, the preparation method comprises the following steps: firstly, taking 35.0 to 47.0 weight percent of recycled aluminum oxide ceramic, 25.0 to 34.0 weight percent of light-burned spinel aggregate, 13.0 to 19.0 weight percent of recycled zirconia corundum bricks, 6.0 to 9.0 weight percent of alpha aluminum oxide, 2.0 to 5.0 weight percent of fused magnesia and 1.5 to 4.5 weight percent of hydratable aluminum oxide as raw materials, adding 3.5 to 4.5 weight percent of binding agent and 0.05 to 0.08 weight percent of fiber, and uniformly mixing, so as to obtain the corundum spinel castable with low thermal conductivity and high corrosion resistance. The method has the characteristics of energy conservation, high efficiency, environment friendliness and low cost; the prepared corundum spinel castable with low thermal conductivity and high corrosion resistance is excellent in thermal shock resistance, high in mechanical strength and relatively high in use temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials for ladles, and particularly relates to a low-thermal-conductivity and high-corrosion-resistance corundum-spinel castable and a preparation method thereof. Background Art

[0002] As important thermal equipment for steelmaking, the consumption of refractory materials of continuous casting ladle and refining ladle outside the furnace accounts for more than 30% of the total consumption of refractory materials in the steel industry, which plays a key role in the consumption of refractory materials per ton of steel. Therefore, the refractory technology of ladle has been one of the important research topics in recent years. In the research on refractory materials for the working layer of ladle, in order to avoid the problem of carbon composite refractory materials introducing [C] into molten steel, researchers have developed high-purity aluminum-magnesium refractory materials based on high-purity synthetic raw materials. Since the promotion of this type of material in the late 1990s, it has been widely accepted by steel mills due to its advantages such as long service life, no carbon, and low content of silicon oxide and iron oxide impurities. High-purity aluminum-magnesium refractory materials mainly include corundum-spinel castables, corundum-magnesium oxide castables and unfired bricks, among which corundum-spinel castables are currently the most used and the most deeply studied.

[0003] Although corundum-spinel castables have been widely used as refractory materials for ladle working linings, the material itself still has the following problems: First, the volume expansion associated with the in-situ spinel formation, although it can make the material structure dense and improve its resistance to slag penetration, there are also disadvantages of cracking and spalling of the material due to excessive expansion; second, high densification often leads to a decrease in the thermal shock resistance of the material, and the material is prone to spalling; third, the reaction between slag and refractory materials is inevitable, and this process easily introduces inclusions into the molten steel, especially large-sized inclusions, which seriously damage the stability of high-quality steel.

[0004] In recent years, great progress has been made in improving the high-temperature strength and thermal shock resistance of corundum-spinel castables, but these advances cannot effectively prevent the castables from reacting with molten steel and slag at high temperatures. The erosion of slag and the structural spalling caused by penetration are the main reasons for the damage of corundum-spinel castable refractory materials. The slag contains a variety of chemical components, which are easy to react with the main components of the refractory materials to form inclusions such as 2MnO·SiO2·Al2O3 and 2CaO·SiO2·Al2O3. The particle size of such inclusions is usually at the micro-nano scale, and it is relatively difficult to float and remove them, becoming one of the main sources of inclusions in molten steel. In addition, the high content of CaO in the refined slag will infiltrate into the castable, which will cause Al2O3+ CA6→CaO·2Al2O3(CA2) →12CaO·7Al2O3(C 12A7) continuous expansion reaction process. This expansion process does not match the thermal expansion coefficient of the castable body, which eventually leads to the gradual appearance of cracks in the reaction permeation layer. During the use of the ladle, the structure of the corresponding part is prone to peeling, resulting in the introduction of large-sized foreign inclusions into the molten steel.

[0005] At present, there are technologies for the preparation and performance optimization of corundum spinel castables, such as the patented technology of "Anti-stripping complex phase corundum spinel castable for refined ladle and preparation method thereof" (CN116041050A), which discloses a patented technology for preparing corundum spinel castable for ladle working layer using fused magnesia-chrome sand, complex phase corundum and aluminum sol as raw materials. A large amount of magnesium-chromium materials are introduced into the raw materials of this method, which has an adverse impact on the environment and causes huge pollution; such as the patented technology of "A carbon-free corundum spinel prefabricated block for ladle working lining and preparation method thereof" (CN116063090A), which discloses A patented technology for preparing carbon-free corundum spinel prefabricated blocks using white corundum, plate-shaped corundum, sintered aluminum-magnesium spinel, active α-Al2O3 powder, calcined α-Al2O3 powder, yttria-stabilized barium aluminum zirconate cement, water reducer and explosion-proof fiber as raw materials has been developed. The expensive yttrium-stabilized barium aluminum zirconate cement is used in the raw materials of this method, which has a high economic cost. In addition, the high-temperature structural stability of yttrium-stabilized barium aluminum zirconate is poor, and cracks are easily generated during thermal shock, which reduces the service life. Another example is "Study on the Corrosion Behavior of Slags with Different Basicities on Corundum-Spinel Castables" (Refractory Materials, 2024). 58(1): 13~18) The literature reported a technology for preparing corundum-spinel castables using sintered corundum particles, defect spinel fine powder, active α-Al2O3 powder, fused magnesia fine powder, and calcium aluminate cement as the main raw materials. This method optimizes the corrosion resistance by introducing defect spinel and forming fine-grained spinel in situ, but the effect is minimal. Hydration defects can easily lead to castable spalling and increase the inclusions in molten steel.

[0006] The above research has made some progress in understanding the erosion mechanism of corundum-spinel castables and improving the erosion resistance of materials, but it has not changed the nature of the materials, that is, the MgO, Al2O3 and other components in the materials are mainly introduced in the form of periclase, corundum or spinel. The particles of these materials may enter the molten steel under the stirring of argon blowing or circulating degassing without being completely corroded in the smelting state, forming Al2O3 inclusions or composite inclusions based on Al2O3, or becoming fine inclusions or large-sized inclusions. No matter which form of inclusions, the adverse effect on the performance of ultra-clean steel is great.

[0007] The present invention uses microporous corundum, lightly calcined spinel and recycled zirconium corundum bricks as main raw materials, and hydrated alumina and aluminum dihydrogen phosphate as binders to prepare high-performance, long-life low thermal conductivity and high corrosion resistance corundum spinel castables with excellent performance. While achieving the non-Ca content in the low thermal conductivity and high corrosion resistance corundum spinel castable, the performance of the low thermal conductivity and high corrosion resistance corundum spinel castable can also be optimized and the service life can be extended. Summary of the invention

[0008] The present invention aims to overcome the defects of the prior art and aims to provide an energy-saving, efficient, green, environmentally friendly and low-cost low thermal conductivity and high corrosion resistance corundum spinel castable and a preparation method thereof. The low thermal conductivity and high corrosion resistance corundum spinel castable prepared by the method has high mechanical strength, good corrosion resistance and long service life, which is of great significance to the promotion of ladle refining process.

[0009] To achieve the above purpose, the technical scheme adopted by the present invention is: first use 35.0~47.0wt% of recycled alumina ceramics and 25.0~34.0wt% of light-burned spinel aggregate, 13.0~19.0wt% of recycled zirconium corundum bricks, 6.0~9.0wt% of α-alumina, 2.0~5.0wt% of fused magnesia, and 1.5~4.5wt% of hydratable alumina as raw materials, and then add 3.5~4.5wt% of binder and 0.05~0.08wt% of fiber, mix them evenly, and obtain low thermal conductivity and high corrosion resistance corundum spinel castable.

[0010] The recycled alumina ceramics are obtained by crushing used high-alumina alumina electronic ceramics, wherein: particles with a particle size between 8 and 5 mm account for 35.0wt%, particles with a particle size between 5 and 3 mm account for 19.0wt%, particles with a particle size between 3 and 1 mm account for 16.0wt%, particles with a particle size between 1 and 0.088 mm account for 8.0wt%, and fine powder with a particle size less than 0.088 mm accounts for 22.0wt%; the porosity of the recycled alumina ceramics is 13 to 17vol.%; the main chemical components of the recycled alumina ceramics are: Al2O3 content ≥99.5wt%, Na2O content ≤0.1wt%.

[0011] Among the light-burned spinel aggregate, particles with a particle size between 5 and 3 mm account for 27.0wt%, particles with a particle size between 3 and 1 mm account for 35.0wt%, particles with a particle size between 1 and 0.088 mm account for 22.0wt%, and fine powder with a particle size less than 0.088 mm accounts for 16.0wt%; the main chemical components of the light-burned spinel aggregate are: MgO content ≥52.0wt%, Al2O3 content ≥47.0wt%, SiO2 content ≤0.07wt%, and Fe2O3 content ≤0.1wt%.

[0012] The recycled zirconium corundum bricks are obtained by crushing the used refractory materials obtained by cutting and grinding the zirconium corundum bricks used in the melting pool of the glass furnace, wherein: particles with a particle size between 3 and 1 mm account for 33.0wt%, particles with a particle size between 1 and 0.088 mm account for 52.0wt%, and fine powder with a particle size less than 0.088 mm accounts for 15.0wt%; the main chemical components of the recycled zirconium corundum bricks are: SiO2 content ≥47.0wt%, Al2O3 content ≥45.0wt%, ZrO2 content ≤5.5wt%, Fe2O3 content ≤1.2wt%, IL ≤0.7wt%.

[0013] The particle size of the α-alumina is less than 0.5 μm; the main chemical components of the α-alumina are: Al2O3 content ≥ 99.7wt%, Na2O content ≤ 0.05wt%.

[0014] The particle size of the fused magnesia is less than 0.088 mm; the main chemical components of the fused magnesia are: MgO content ≥ 96.7wt%, SiO2 content ≤ 0.5wt%.

[0015] The particle size of the hydrated alumina is less than 0.074 mm; the main chemical components of the hydrated alumina are: Al2O3 content ≥ 64.5wt%, Na2O content ≤ 0.15wt%, IL ≤ 18.9wt%.

[0016] The binder is one of aluminum dihydrogen phosphate with a concentration of 20wt%, 30wt% and 40wt%.

[0017] The fiber is one of aluminum silicate fiber, aluminum oxide fiber and basalt fiber.

[0018] Due to the adoption of the above technical solution, the present invention has the following positive effects compared with the prior art: 1. Using recycled high-alumina alumina ceramics to replace the conventionally selected plate-shaped corundum, white corundum or brown corundum can greatly reduce the economic cost of the material. At the same time, the microcracks in the used material are helpful to introduce micropores to optimize the high-temperature and low-thermal conductivity of the castable. The prepared low-thermal-conductivity and high-corrosion-resistant corundum spinel castable has a flexural strength of 10.9~15.1MPa and a compressive strength of 67.4~79.6MPa after baking at 110℃×24h; after sintering at 1550℃×3h, the flexural strength is>29.3MPa, the compressive strength is 108.8~145.8MPa, and the linear change rate is ±0.02%; the high-temperature flexural strength at 1400℃ is 22.4~28.2MPa; the thermal conductivity coefficient at the test temperature of 1000℃ is less than 2.5 W / (m·K), and the performance is better than similar products on the market.

[0019] 2. Use hydrated alumina instead of calcium aluminate cement as the conventional choice of binder to achieve Ca-free low thermal conductivity and high corrosion resistance corundum spinel castable, avoid the production of low melting products such as calcite during high temperature use, optimize the high temperature performance of the castable, and extend its service life.

[0020] 3. Using aluminum dihydrogen phosphate as a binder, on the one hand, the acidity of aluminum dihydrogen phosphate is conducive to inhibiting the hydrolysis reaction of fused magnesia and hydrated alumina in the matrix, and on the other hand, aluminum dihydrogen phosphate can react with alumina to form aluminum phosphate, forming a new ceramic bonding enhancement phase, further optimizing the bonding strength of the matrix.

[0021] Therefore, the present invention has the characteristics of energy saving, high efficiency, green environmental protection and low cost; the low thermal conductivity and high corrosion resistance corundum spinel castable has high mechanical strength, good corrosion resistance and long service life. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0023] To avoid repetition, the relevant technical parameters involved in this specific implementation are first described as follows, and will not be repeated in the embodiments: The recycled alumina ceramics are obtained by crushing used high-alumina alumina electronic ceramics, wherein: particles with a particle size between 8 and 5 mm account for 35.0wt%, particles with a particle size between 5 and 3 mm account for 19.0wt%, particles with a particle size between 3 and 1 mm account for 16.0wt%, particles with a particle size between 1 and 0.088 mm account for 8.0wt%, and fine powder with a particle size less than 0.088 mm accounts for 22.0wt%; the porosity of the recycled alumina ceramics is 13 to 17vol.%; the main chemical components of the recycled alumina ceramics are: Al2O3 content ≥99.5wt%, Na2O content ≤0.1wt%.

[0024] Among the light-burned spinel aggregate, particles with a particle size between 5 and 3 mm account for 27.0wt%, particles with a particle size between 3 and 1 mm account for 35.0wt%, particles with a particle size between 1 and 0.088 mm account for 22.0wt%, and fine powder with a particle size less than 0.088 mm accounts for 16.0wt%; the main chemical components of the light-burned spinel aggregate are: MgO content ≥52.0wt%, Al2O3 content ≥47.0wt%, SiO2 content ≤0.07wt%, and Fe2O3 content ≤0.1wt%.

[0025] The recycled zirconium corundum bricks are obtained by crushing the used refractory materials obtained by cutting and grinding the zirconium corundum bricks used in the melting pool of the glass furnace, wherein: particles with a particle size between 3 and 1 mm account for 33.0wt%, particles with a particle size between 1 and 0.088 mm account for 52.0wt%, and fine powder with a particle size less than 0.088 mm accounts for 15.0wt%; the main chemical components of the recycled zirconium corundum bricks are: SiO2 content ≥47.0wt%, Al2O3 content ≥45.0wt%, ZrO2 content ≤5.5wt%, Fe2O3 content ≤1.2wt%, IL ≤0.7wt%.

[0026] The particle size of the α-alumina is less than 0.5 μm; the main chemical components of the α-alumina are: Al2O3 content ≥ 99.7wt%, Na2O content ≤ 0.05wt%.

[0027] The particle size of the fused magnesia is less than 0.088 mm; the main chemical components of the fused magnesia are: MgO content ≥ 96.7wt%, SiO2 content ≤ 0.5wt%.

[0028] The particle size of the hydrated alumina is less than 0.074 mm; the main chemical components of the hydrated alumina are: Al2O3 content ≥ 64.5wt%, Na2O content ≤ 0.15wt%, IL ≤ 18.9wt%.

[0029] The binder is one of aluminum dihydrogen phosphate with a concentration of 20wt%, 30wt% and 40wt%.

[0030] The fiber is one of aluminum silicate fiber, aluminum oxide fiber and basalt fiber.

[0031] Example 1 A low thermal conductivity and high corrosion resistance corundum spinel castable and a preparation method thereof. First, 35.0-37.0wt% of recycled alumina ceramics and 32.5-34.0wt% of light-burned spinel aggregate, 14.0-15.0wt% of recycled zirconium corundum bricks, 7.5-8.0wt% of α-alumina, 4.5-5.0wt% of fused magnesia, and 4.0-4.5wt% of hydrated alumina are used as raw materials, and then 3.5-4.5wt% of aluminum dihydrogen phosphate with a concentration of 40wt% and 0.05-0.08wt% of aluminum silicate fiber are added and mixed evenly to obtain a low thermal conductivity and high corrosion resistance corundum spinel castable.

[0032] The low thermal conductivity and high corrosion resistance corundum spinel castable prepared in this embodiment is tested: after baking at 110°C×24h, the flexural strength is 11.8~13.5MPa, and the compressive strength is 68.9~72.2MPa; after sintering at 1550°C×3h, the flexural strength is>29.3MPaMPa, the compressive strength is 121.6~132.5 MPa, and the linear change rate is ±0.02%; the high temperature flexural strength at 1400°C is 22.4~24.6MPa; the thermal conductivity at the test temperature of 1000°C is 2.3~2.4 W / (m·K).

[0033] Example 2 A low thermal conductivity and high corrosion resistance corundum spinel castable and a preparation method thereof. First, 32.5-34.0wt% of recycled alumina ceramics and 31.0-32.5wt% of light-burned spinel aggregate, 18.0-19.0wt% of recycled zirconium corundum bricks, 6.0-6.5wt% of α-alumina, 4.0-4.5wt% of fused magnesia, and 3.5-4.0wt% of hydrated alumina are used as raw materials, and then 3.5-4.5wt% of aluminum dihydrogen phosphate with a concentration of 30wt% and 0.05-0.08wt% of alumina fiber are added and mixed evenly to obtain a low thermal conductivity and high corrosion resistance corundum spinel castable.

[0034] The low thermal conductivity and high corrosion resistance corundum spinel castable prepared in this embodiment is tested: after baking at 110°C×24h, the flexural strength is 12.4~14.3MPa, and the compressive strength is 73.1~76.4MPa; after sintering at 1550°C×3h, the flexural strength is>29.3MPa, the compressive strength is 125.5~142.3 MPa, and the linear change rate is ±0.01%; the high temperature flexural strength at 1400°C is 24.1~26.6MPa; the thermal conductivity at the test temperature of 1000°C is 2.4~2.5 W / (m·K).

[0035] Example 3 A low thermal conductivity and high corrosion resistance corundum spinel castable and a preparation method thereof. First, 39.0-41.0wt% of recycled alumina ceramics and 29.5-31.0wt% of light-burned spinel aggregate, 15.0-16.0wt% of recycled zirconium corundum bricks, 8.5-9.0wt% of α-alumina, 3.5-4.0wt% of fused magnesia, and 3.0-3.5wt% of hydrated alumina are used as raw materials, and then 3.5-4.5wt% of 20wt% aluminum dihydrogen phosphate and 0.05-0.08wt% of basalt fiber are added and mixed evenly to obtain a low thermal conductivity and high corrosion resistance corundum spinel castable.

[0036] The low thermal conductivity and high corrosion resistance corundum spinel castable prepared in this embodiment is tested: after baking at 110°C×24h, the flexural strength is 11.5~13.7MPa, and the compressive strength is 70.7~74.1MPa; after sintering at 1550°C×3h, the flexural strength is>29.3MPa, the compressive strength is 117.2~129.7 MPa, and the linear change rate is ±0.00%; the high temperature flexural strength at 1400°C is 23.5~25.7MPa; the thermal conductivity at the test temperature of 1000°C is 2.2~2.3 W / (m·K).

[0037] Example 4 A low thermal conductivity and high corrosion resistance corundum spinel castable and a preparation method thereof. First, 45.0-47.0wt% of recycled alumina ceramics, 28.0-29.5wt% of light-burned spinel aggregate, 13.0-14.0wt% of recycled zirconium corundum bricks, 6.5-7.0wt% of α-alumina, 3.0-3.5wt% of fused magnesia, and 2.0-2.5wt% of hydrated alumina are used as raw materials, and then 3.5-4.5wt% of aluminum dihydrogen phosphate with a concentration of 40wt% and 0.05-0.08wt% of aluminum silicate fiber are added and mixed evenly to obtain a low thermal conductivity and high corrosion resistance corundum spinel castable.

[0038] The low thermal conductivity and high corrosion resistance corundum spinel castable prepared in this embodiment is tested: after baking at 110°C×24h, the flexural strength is 10.9~12.2MPa, and the compressive strength is 67.4~71.1MPa; after sintering at 1550°C×3h, the flexural strength is>29.3MPa, the compressive strength is 108.8~122.7MPa, and the linear change rate is ±0.02%; the high temperature flexural strength at 1400°C is 24.5~26.1MPa; the thermal conductivity at the test temperature of 1000°C is 2.3~2.4 W / (m·K).

[0039] Example 5 A low thermal conductivity and high corrosion resistance corundum spinel castable and a preparation method thereof. First, 41.0-43.0wt% of recycled alumina ceramics, 26.5-28.0wt% of light-burned spinel aggregate, 17.0-180wt% of recycled zirconium corundum bricks, 7.0-7.5wt% of α-alumina, 2.5-3.0wt% of fused magnesia, and 2.5-3.0wt% of hydrated alumina are used as raw materials, and then 3.5-4.5wt% of aluminum dihydrogen phosphate with a concentration of 30wt% and 0.05-0.08wt% of alumina fiber are added and mixed evenly to obtain a low thermal conductivity and high corrosion resistance corundum spinel castable.

[0040] The low thermal conductivity and high corrosion resistance corundum spinel castable prepared in this embodiment is tested: after baking at 110°C×24h, the flexural strength is 12.2~14.5MPa, and the compressive strength is 71.1~74.9MPa; after sintering at 1550°C×3h, the flexural strength is>29.3MPa, the compressive strength is 120.2~137.5 MPa, and the linear change rate is ±0.01%; the high temperature flexural strength at 1400°C is 25.9~27.2MPa; the thermal conductivity at the test temperature of 1000°C is 2.2~2.3 W / (m·K).

[0041] Example 6 A low thermal conductivity and high corrosion resistance corundum spinel castable and a preparation method thereof. First, 43.0-45.0wt% of recycled alumina ceramics, 25.0-26.5wt% of light-burned spinel aggregate, 16.0-17.0wt% of recycled zirconium corundum bricks, 8.0-8.5wt% of α-alumina, 2.0-2.5wt% of fused magnesia, and 1.5-2.0wt% of hydrated alumina are used as raw materials, and then 3.5-4.5wt% of aluminum dihydrogen phosphate with a concentration of 40wt% and 0.05-0.08wt% of basalt fiber are added and mixed evenly to obtain a low thermal conductivity and high corrosion resistance corundum spinel castable.

[0042] The low thermal conductivity and high corrosion resistance corundum spinel castable prepared in this embodiment is tested: after baking at 110°C×24h, the flexural strength is 12.8~15.1 MPa, and the compressive strength is 75.2~79.6 MPa; after sintering at 1550°C×3h, the flexural strength is>29.3MPa, the compressive strength is 127.5~145.8 MPa, and the linear change rate is ±0.01%; the high temperature flexural strength at 1400°C is 26.8~28.2 MPa; the thermal conductivity at the test temperature of 1000°C is 2.4~2.5 W / (m·K).

[0043] Due to the adoption of the above technical solution, this specific implementation has the following positive effects compared with the prior art: 1. Using recycled high-alumina alumina ceramics to replace the conventionally selected plate-shaped corundum, white corundum or brown corundum can greatly reduce the economic cost of the material. At the same time, the microcracks in the used material are helpful to introduce micropores to optimize the high-temperature and low-thermal conductivity of the castable. The prepared low-thermal-conductivity and high-corrosion-resistant corundum spinel castable has a flexural strength of 10.9~15.1MPa and a compressive strength of 67.4~79.6MPa after baking at 110℃×24h; after sintering at 1550℃×3h, the flexural strength is>29.3MPa, the compressive strength is 108.8~145.8MPa, and the linear change rate is ±0.02%; the high-temperature flexural strength at 1400℃ is 22.4~28.2MPa; the thermal conductivity at the test temperature of 1000℃ is 2.2~2.5 W / (m·K), which is better than similar products on the market.

[0044] 2. Use hydrated alumina instead of calcium aluminate cement as the conventional choice of binder to achieve Ca-free low thermal conductivity and high corrosion resistance corundum spinel castable, avoid the production of low melting products such as calcite during high temperature use, optimize the castable's resistance to slag erosion and extend its service life.

[0045] 3. Using aluminum dihydrogen phosphate as a binder, on the one hand, the acidity of aluminum dihydrogen phosphate is conducive to inhibiting the hydrolysis reaction of fused magnesia and hydrated alumina in the matrix, and on the other hand, aluminum dihydrogen phosphate can react with alumina to form aluminum phosphate, forming a new ceramic bonding enhancement phase, further optimizing the bonding strength of the matrix.

[0046] Therefore, the present invention has the characteristics of energy saving, high efficiency, green environmental protection and low cost; the low thermal conductivity and high corrosion resistance corundum spinel castable has high mechanical strength, excellent thermal shock stability and long service life, which is of great significance to the promotion of ladle refining process.

[0047] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a low thermal conductivity and high corrosion resistance corundum spinel castable, characterized in that: First, 35.0~47.0wt% of recycled alumina ceramics, 25.0~34.0wt% of light-burned spinel aggregate, 13.0~19.0wt% of recycled zirconium corundum bricks, 6.0~9.0wt% of α-alumina, 2.0~5.0wt% of fused magnesia, and 1.5~4.5wt% of hydratable alumina are used as raw materials, and 3.5~4.5wt% of a binder and 0.05~0.08wt% of fiber are added and mixed evenly to obtain a low thermal conductivity and high corrosion resistance corundum spinel castable.

2. The method for preparing the low thermal conductivity and high corrosion resistance corundum spinel castable according to claim 1, characterized in that: The recycled alumina ceramics are obtained by crushing used high-alumina alumina electronic ceramics, wherein: particles with a particle size between 8 and 5 mm account for 35.0wt%, particles with a particle size between 5 and 3 mm account for 19.0wt%, particles with a particle size between 3 and 1 mm account for 16.0wt%, particles with a particle size between 1 and 0.088 mm account for 8.0wt%, and fine powder with a particle size less than 0.088 mm accounts for 22.0wt%; the porosity of the recycled alumina ceramics is 13 to 17vol.%; the main chemical components of the recycled alumina ceramics are: Al2O3 content ≥99.5wt%, Na2O content ≤0.1wt%.

3. The method for preparing the low thermal conductivity and high corrosion resistance corundum spinel castable according to claim 1, characterized in that: Among the light-burned spinel aggregate, particles with a particle size between 5 and 3 mm account for 27.0wt%, particles with a particle size between 3 and 1 mm account for 35.0wt%, particles with a particle size between 1 and 0.088 mm account for 22.0wt%, and fine powder with a particle size less than 0.088 mm accounts for 16.0wt%; the main chemical components of the light-burned spinel aggregate are: MgO content ≥52.0wt%, Al2O3 content ≥47.0wt%, SiO2 content ≤0.07wt%, and Fe2O3 content ≤0.1wt%.

4. The method for preparing the low thermal conductivity and high corrosion resistance corundum spinel castable according to claim 1, characterized in that: The recycled zirconium corundum bricks are obtained by crushing the used refractory materials obtained by cutting and grinding the zirconium corundum bricks used in the melting pool of the glass furnace, wherein: particles with a particle size between 3 and 1 mm account for 33.0wt%, particles with a particle size between 1 and 0.088 mm account for 52.0wt%, and fine powder with a particle size less than 0.088 mm accounts for 15.0wt%; the main chemical components of the recycled zirconium corundum bricks are: SiO2 content ≥37.0wt%, Al2O3 content ≥35.0wt%, ZrO2 content ≤25.5wt%, Fe2O3 content ≤1.2wt%, IL ≤0.2wt%.

5. The method for preparing the low thermal conductivity and high corrosion resistance corundum spinel castable according to claim 1, characterized in that: The particle size of the α-alumina is less than 0.5 μm; the main chemical components of the α-alumina are: Al2O3 content ≥ 99.7wt%, Na2O content ≤ 0.05wt%.

6. The method for preparing the low thermal conductivity and high corrosion resistance corundum spinel castable according to claim 1, characterized in that: The particle size of the fused magnesia is less than 0.088 mm; the main chemical components of the fused magnesia are: MgO content ≥ 96.7wt%, SiO2 content ≤ 0.5wt%.

7. The method for preparing the low thermal conductivity and high corrosion resistance corundum spinel castable according to claim 1, characterized in that: The particle size of the hydrated alumina is less than 0.074 mm; the main chemical components of the hydrated alumina are: Al2O3 content ≥ 64.5wt%, Na2O content ≤ 0.15wt%, IL ≤ 18.9wt%.

8. The method for preparing the low thermal conductivity and high corrosion resistance corundum spinel castable according to claim 1, characterized in that: The binder is one of aluminum dihydrogen phosphate with a concentration of 20wt%, 30wt% and 40wt%.

9. The method for preparing the low thermal conductivity and high corrosion resistance corundum spinel castable according to claim 1, characterized in that: The fiber is one of aluminum silicate fiber, aluminum oxide fiber and basalt fiber.

10. A low thermal conductivity and high corrosion resistance corundum spinel castable, wherein the low thermal conductivity and high corrosion resistance corundum spinel castable is prepared by the preparation method of the low thermal conductivity and high corrosion resistance corundum spinel castable according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Anti-stripping complex-phase corundum spinel castable for refining steel ladle and preparation method of anti-stripping complex-phase corundum spinel castable

    CN116041050A

  • Steel ladle working lining carbon-free corundum spinel precast block and preparation method thereof

    CN116063090A

Cited By

  • Hot-state gunning mix for steel ladle and preparation method of hot-state gunning mix

    CN120607409A